1998
DOI: 10.4131/jshpreview.7.245
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Liquid Rubidium and Liquid Sodium under Pressure.

Abstract: a present address. SPring -8 , JAERI, Kamigori, Aiko gun, Hyogo 678-12, Japan X-ray diffraction for liquid Rb and liquid Na has been measured under pressure up to 6 GPa using synchrotron radiation. Volume dependences of static structure factor S(Q) and pair distribution function g(r) were obtained to the volume range v(=V/V0) of 0.52 for liquid Rb and to v of 0.73 for liquid Na to investigate the effect of the electronic change on the structure of liquid metals. With increasing pressure, the peaks of S(Q) of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The first reported in situ diffraction experiment of a liquid at high-p measured the structure of the liquid alkali sodium (Na) to 4.3 GPa [145]. Subsequent studies of alkali liquids were performed using the MAX-80 and MAX-90 large volume apparatus at the PF reporting the structure of liquid Na to 5.1 GPa [368], liquid Rb to 6.1 GPa [369], and liquid Cs to 4.3 GPa [370]. The diffraction data revealed the liquid alkali's follow a uniform compression model at low-p up to at least ∼ 3-4 GPa with a slight deviation from ideal behaviour observed for liquid Rb and Cs at higher-p to accommodate a slight increase in coordination number [369].…”
Section: Alkali Metals: Simple To Complex Liquid Structurementioning
confidence: 99%
“…The first reported in situ diffraction experiment of a liquid at high-p measured the structure of the liquid alkali sodium (Na) to 4.3 GPa [145]. Subsequent studies of alkali liquids were performed using the MAX-80 and MAX-90 large volume apparatus at the PF reporting the structure of liquid Na to 5.1 GPa [368], liquid Rb to 6.1 GPa [369], and liquid Cs to 4.3 GPa [370]. The diffraction data revealed the liquid alkali's follow a uniform compression model at low-p up to at least ∼ 3-4 GPa with a slight deviation from ideal behaviour observed for liquid Rb and Cs at higher-p to accommodate a slight increase in coordination number [369].…”
Section: Alkali Metals: Simple To Complex Liquid Structurementioning
confidence: 99%
“…Pressure dependences of the structure of liquids have been studied for various liquid metals by means of x-ray diffraction measurements under pressure using synchrotron radiation [1][2][3]. The measurements have revealed that contractions of liquid alkali metals are almost uniform [3][4][5], whereas those of liquids in which atoms are covalently bonded such as liquid selenium [6,7], liquid tellurium [8] and liquid iodine [9,10] are anisotropic. In these covalent liquids, the nearest neighbour distance increases with increasing pressure in spite of volume contraction.…”
Section: Introductionmentioning
confidence: 99%
“…1 Consequently, it is accepted that fractal structures spread into disordered the structure of metallic glasses to the fractal network and discovered that metallic glasses 5 have fractal characteristics within the medium-range length scale, as indicated by the 2.31 6 power law scaling of the first peak position of the structure factor with the atomic 7 volume. 2 Subsequently, non-integral 2.5 power law scaling was discovered in metallic 8 glasses under pressure conditions, not only in reciprocal space but also in real space, and 9 it extended beyond the first peak, depending on the specific system. Any non-integral 10 power corresponds to a fractal dimensionality, D f .…”
mentioning
confidence: 99%
“…8,9 In metallic glasses and liquid alkali metal systems, a single scaling exponent, D f , 15 characterizes the fractal structure of the object. 16 17 Due to the coexistence of metallic and covalent bonding, gallium, a rich polymorphism 18 metal, exhibits unusual and unique physical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation